2019
DOI: 10.2319/062818-481.1
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic properties of human periodontal ligament: Effects of the loading frequency and location

Abstract: Objectives: To determine the viscoelastic properties of the human periodontal ligament (PDL) using dynamic mechanical analysis (DMA). Materials and Methods: This study was carried out on three human maxillary jaw segments containing six upper central incisors and four lateral incisors. DMA was used to investigate the mechanical response of the human PDL. Dynamic sinusoidal loading was carried out with an amplitude of 3 N and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 19 publications
3
14
0
Order By: Relevance
“…Consistent with previous findings of the human PDL revealing a frequency-related viscoelasticity under dynamic tension [ 12 ], our current experiment yielded similar results when the analysis was extended to compressive forces. However, the dynamic moduli were much greater in the compression test than in the tension test (E’ from 0.808 MPa to 7.274 MPa, E'' from 0.087 MPa to 0.891 MPa).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous findings of the human PDL revealing a frequency-related viscoelasticity under dynamic tension [ 12 ], our current experiment yielded similar results when the analysis was extended to compressive forces. However, the dynamic moduli were much greater in the compression test than in the tension test (E’ from 0.808 MPa to 7.274 MPa, E'' from 0.087 MPa to 0.891 MPa).…”
Section: Discussionsupporting
confidence: 92%
“…Due to collagen fibers’ resistance against tensile loads and ground substance tolerance against compressive loads, the PDL has displayed different mechanical responses under tension and compressive loadings [ 11 ]. We clarified the viscoelastic properties of the human PDL under dynamic tension in our former study, in which the viscoelasticity of PDL was believed to be related to frequency, tooth position, and root level [ 12 ]. However, its mechanical behavior under dynamic compression loading is still to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this method may be a good model for fluid exudation in tension due to Poisson effects, particularly in a highly anisotropic tissue. Recent studies investigating dynamic tensile function have also demonstrated heterogeneity in PDL viscoelastic properties with root level but not between mesial and distal surfaces (Uhlir et al, 2017;Wu et al, 2019Wu et al, , 2018. Our data consistently also showed limited differences between the mesial and distal surfaces, but instead demonstrated large variability in bucco-lingual properties, which to our knowledge has not been measured in previous studies.…”
Section: Resultssupporting
confidence: 80%
“…Using the tangent of the phase angle, termed the loss factor tanδ, as a measurement of the damping capacity of materials, [ 27 ] we found that the measured average loss factor of the PIL (tanδ ≈ 0.053 ± 0.008) was approximately five times higher than that of the non‐modified Ti substrate (0.009 ± 0.0010) at a variety of frequencies (Figure 2c). The value of tanδ also approached that of natural PDL over a wide range of frequencies (e.g., the tanδ of human PDL is ≈0.078–0.13 at 0.5–10 Hz, [ 28 ] and bovine PDL is ≈0.04–0.08 at 0.01–100 Hz). [ 14 ] Further, the average tanδ value of amorphous titania (0.012 ± 0.002) substantially exceeded that of crystalline titania (0.004 ± 0.002) at 1–100 Hz (Figure S14a, Supporting Information).…”
Section: Resultsmentioning
confidence: 88%